miR-21 Expression Determines the Early Vaccine Immunity Induced by LdCen−/− Immunization - Gannavaram, Sreenivas; Bhattacharya, Parna; Siddiqui, Abid; Ismail, Nevien; Madhavan, Subha; Nakhasi, Hira L. (Frontiers in Immunology, 2019)
No vaccine exists against visceral leishmaniasis. Towards developing vaccines against VL, we have reported previously on the immunogenicity of live attenuated LdCen-/- parasites in animal models. Immunization with LdCen-/- parasites has been shown induce durable protective immunity in pre-clinical animal models. Although the innate immune responses favoring a Th1 type immunity are produced following LdCen-/- immunization, the molecular determinants of such responses remain unknown. To identify early biomarkers of immunogenicity associated with live attenuated parasitic vaccines, we infected macrophages derived from healthy human blood donors with LdCen-/- or LdWT parasites ex vivo and compared the early gene expression profiles. In addition to altered expression of immune related genes, we identified several microRNAs that regulate important cytokine genes, significantly altered in LdCen-/- infection compared to LdWT infection. Importantly, we found that LdCen-/- infection suppresses the expression of microRNA-21 (miR-21) in human macrophages, which negatively regulates IL12, compared to LdWT infection. In murine DC experiments, LdCen-/- infection showed a reduced miR-21 expression with a concomitant induction of IL12. Silencing of miR-21 using specific inhibitors resulted in an augmented induction of IL12 in LdWT infected BMDCs, illustrating the role of miR-21 in LdWT mediated suppression of IL12. Further, exosomes isolated from LdCen-/- infected DCs contained significantly reduced levels of miR-21 compared to LdWT infection, that promoted proliferation of CD4+ T cells in vitro. Similar miR-21 mediated IL12 regulation was also observed in ex vivo human macrophage infection experiments indicating that miR-21 plays a role in early IL12 mediated immunity. Our studies demonstrate that LdCen-/- infection suppresses miR-21 expression, enables IL12 mediated induction of adaptive immunity including proliferation of antigen experienced CD4+ T cells and development of a Th1 immunity, and suggest that miR-21 could be an important biomarker for LdCen-/- vaccine immunity in human clinical trials.